Digitalisasi Edukasi Kesehatan: Pengaruh E-Book Aksi SADARI bagi Kader - Kusmihardianti, Baiq Nabila; Rumintang, Baiq Iin; Pratiwi, Intan Gumilang (Indonesian Journal Publisher, 2025)
Background: Breast cancer is the most prevalent cancer among women globally, with 2,296,840 cases and 666,103 deaths. In Indonesia, breast cancer ranks first, with 66,271 new cases and 22,598 deaths in 2022. Health cadres play a key role in prevention and health education in the community. E-books offer an accessible and effective solution to enhance health cadres’ knowledge, providing easy access to educational content anytime and anywhere, supporting promotive and preventive health efforts. Objective: To assess the impact of e-book Aksi SADARI educational media on health cadres' knowledge regarding early breast cancer detection at Babakan Health Center. Method: This study employed a pre-experimental design with a One Group Pretest-Posttest design. A sample of 70 health cadres was selected from a population of 203. Data were analyzed using the Wilcoxon signed-rank test. Results: This study found that most respondents were over 35 years old (60%), had a high school education (77.1%), were housewives (87.1%), and had served as health cadres for over 5 years (54.3%). Prior to the intervention, 68.6% had low knowledge levels. After receiving education through an e-book, 85.7% demonstrated good knowledge. The Wilcoxon signed-rank test showed a significant improvement in knowledge (p = 0.000; p < 0.05). Conclusion: E-book Aksi SADARI educational media effectively improved health cadres' knowledge on early breast cancer detection at Babakan Health Center in 2025.